До проблеми оперативно-розшукової протидії незаконному обігу вогнепальної зброї у мережі “Інтернет” - Ковальова, Аліна Ігорівна; Телійчук, Віталій Григорович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The article is devoted to the study of the current problem of operational and investigative countermeasures against the illegal circulation of firearms on the Internet. The author examines the current challenges and trends related to the arms trade through digital platforms. The methods and technologies used by criminals to circumvent the law and hide their tracks are analyzed. Also considered are possible ways to increase the effectiveness of operative and investigative measures to counter this type of illegal activity in the online space.